Psychological effects of sodium valproate and carbamazepine in epilepsy. Issue 11 (November 1992) - Stores, G; Williams, P L; Styles, E; Zaiwalla, Z
Abstract : Information from standardised tests of intelligence, school attainments, attention, memory and visuomotor function, together with parent and teacher questionnaire information about various aspects of behaviour, was obtained for 63 schoolchildren with newly diagnosed epilepsy before treatment with sodium valproate or carbamazepine, and again at intervals for a total period of 12 months. The same information was collected on 47 matched controls. The children with epilepsy represented those under non-specialised paediatric care. The result showed that both drugs were effective in most cases at modest dosage without causing notable psychological effects 12 months into treatment. Modest and temporary adverse cognitive effects seen earlier in treatment could have been the result of uncontrolled seizure discharge. Improved function was the same in children with epilepsy and controls. Some psychological abnormalities in the children with epilepsy were evident before treatment suggesting early unwanted effects of the epileptic process itself.